Breaking the oceanic lithosphere of a subducting slab: The 2013 Khash, Iran earthquake. Issue 1 (8th January 2014) - Barnhart, William D.; Hayes, Gavin P.; Samsonov, Sergey V.; Fielding, Eric J.; Seidman, Lily E.
Abstract [1] Large intermediate‐depth, intraslab normal‐faulting earthquakes are a common, dangerous, but poorly understood phenomenon in subduction zones owing to a paucity of near‐field geophysical observations. Seismological and high‐quality geodetic observations of the 2013 Mw7.7 Khash, Iran earthquake reveal that at least half of the oceanic lithosphere, including the mantle and entire crust, ruptured in a single earthquake, confirming with unprecedented resolution that large earthquakes can nucleate in and rupture through the oceanic mantle. A rupture width of at least 55 km is required to explain both Interferometric Synthetic Aperture Radar observations and teleseismic waveforms, with the majority of slip occurring in the oceanic mantle. Combining our well‐constrained earthquake slip distributions with the causative fault orientation and geometry of the local subduction zone, we hypothesize that the Khash earthquake likely occurred as the combined result of slab‐bending forces and dehydration of hydrous minerals along a preexisting fault formed prior to subduction.